Influence of Stress Path on Stress Memory and Stress Fracturing in Brittle Rocks - Bahrani, Navid; Valley, Benoît; Kaiser, Peter K. (My University, 2019)
A two-dimensional numerical model based on the Distinct Element Method, previously calibrated to the laboratory properties of undamaged and damaged Lac du Bonnet (LdB) granite, was used to investigate the influence of stress path on the development of stress memory and stress fracturing in brittle rocks. Various cycles of loading and unloading, similar to those imposed during Kaiser Effect tests, were first applied to undamaged numerical specimens of LdB granite. The results of Kaiser Effect test simulations were found to be consistent with those of published laboratory and numerical investigations. Further simulations were conducted to investigate the influence of stress path resulting from the excavation of a tunnel on the depth of stress fracturing around the excavation boundary. For this purpose, the stress paths at points on and near the tunnel wall, obtained from a continuum finite element model, were applied to the calibrated numerical specimen. It was found that the amount of damage in the numerical specimens decreases rapidly with increasing distance from the excavation wall. The findings of this research shed some light on the influence of stress path and grain-scale heterogeneity on stress memory in brittle rocks and stress fracturing around underground openings.